CT ventilation functional image-based IMRT treatment plans are comparable to SPECT ventilation functional image-based plans. Issue 3 (March 2016) - Kida, Satoshi; Bal, Matthieu; Kabus, Sven; Negahdar, Mohammadreza; Shan, Xin; Loo, Billy W.; Keall, Paul J.; Yamamoto, Tokihiro
Abstract: Purpose: To investigate the hypothesis that CT ventilation functional image-based IMRT plans designed to avoid irradiating highly-functional lung regions are comparable to single-photon emission CT (SPECT) ventilation functional image-based plans. Methods and materials: Three IMRT plans were created for eight thoracic cancer patients using: (1) CT ventilation functional images, (2) SPECT ventilation functional images, and (3) anatomic images (no functional images). CT ventilation images were created by deformable image registration of 4D-CT image data sets and quantitative analysis. The resulting plans were analyzed for the relationship between the deviations of CT-functional plan metrics from anatomic plan metrics ( Δ CT-anatomic ) and those of SPECT-functional plans ( Δ SPECT-anatomic ), and moreover for agreements of various metrics between the CT-functional and SPECT-functional plans. Results: The relationship between Δ CT-anatomic and Δ SPECT-anatomic was strong (e.g., R = 0.94; linear regression slope 0.71). The average differences and 95% limits of agreement between the CT-functional and SPECT-functional plan metrics (except for monitor units) for various structures were mostly less than 1% and 2%, respectively. Conclusions: This study demonstrated a reasonable agreement between the CT ventilation functional image-based IMRT plans and SPECT-functional plans, suggesting the potential for CT ventilation imaging to serve as a surrogate for SPECT ventilation in functional image-guided radiotherapy.